Enamel pretreatment with Er:YAG laser: effects on the microleakage of fissure sealant in fluorosed teeth - Mahtab Memarpour; Nasrin Kianimanesh; Bahareh Shayeghi (Korean Academy of Conservative Dentistry, 2014)
Objectives The purpose of this in vitro study was to evaluate the microleakage and penetration of fissure sealant in permanent molar teeth with fluorosis after pretreatment of the occlusal surface. Materials and Methods A total of 120 third molars with mild dental fluorosis were randomly divided into 6 groups (n = 20). The tooth surfaces were sealed with an unfilled resin fissure sealant (FS) material. The experimental groups included: 1) phosphoric acid etching (AE) + FS (control); 2) AE + One-Step Plus (OS, Bisco) + FS; 3) bur + AE + FS; 4) bur + AE + OS + FS; 5) Er:YAG laser + AE + FS; and 6) Er:YAG laser + AE + OS + FS. After thermocycling, the teeth were immersed in 0.5% fuchsin and sectioned. Proportions of mircoleakage (PM) and unfilled area (PUA) were measured by digital microscope. Results Overall, there were significant differences among all groups in the PM (p = 0.00). Group 3 showed the greatest PM, and was significantly different from groups 2 to 6 (p < 0.05). Group 6 showed the lowest PM. Pretreatment with Er:YAG with or without adhesive led to less PM than bur pretreatment. There were no significant differences among groups in PUA. Conclusions Conventional acid etching provided a similar degree of occlusal seal in teeth with fluorosis compared to those pretreated with a bur or Er:YAG laser. Pretreatment of pits and fissures with Er:YAG in teeth with fluorosis may be an alternative method before fissure sealant application.